MSME Entrepreneurial Assistance in Sumbersekar Village using E-commerce and Marketplace Applications - Meme Susilowati; Yudhi Kurniawan; Rudy Setiawan (Journal of Community Practice and Social Welfare, 2022)
The strategic issue faced by the Sumbersekar Village government located in the Dau sub-district, Malang Regency in 2020 is the lack of community welfare development, despite the availability of superior human resources so which caused the stunting among rural communities. One of those lacks was community economic infrastructure development. The purpose of the MSME (Micro, Small and Medium Enterprises) Entrepreneurial Assistance activity in Sumbersekar Village is to provide IT infrastructure and its briefing to support MSME entrepreneurial economic activities amid the COVID-19 pandemic. The application in this activity expects to be solution (infrastructure). The activity was carried out through 6 stages: Expert judgment; Evaluation and revision of infrastructure; Developing curriculum and modules; Socialization and recruiting participants; Training and mentoring; and Evaluation of activities. The results of the overall evaluation are: The training is limited to participants and with a strict process because it is still in the PPKM (Indonesian abbreviation version of Implementation of Restrictions on Social Activities) period, the training facilities in the village are less than optimal so they are not comfortable for participants, the material deliverances is less than optimal due to meeting restrictions and limited absorption capacity of participants. The conclusion of the activity is: There is an increase in the expertise of the MSME entrepreneurship in Sumbersekar Village, MSMEs have a new way of doing entrepreneurship digitally using e-commerce and social media. The implementation of IT briefing for MSME entrepreneurs so that they can maintain their business amid this pandemic by migrating to e-commerce and marketplaces.